2022
DOI: 10.3390/bioengineering9020043
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanism of Malignant Transformation of Balb/c-3T3 Cells Induced by Long-Term Exposure to 1800 MHz Radiofrequency Electromagnetic Radiation (RF-EMR)

Abstract: Purpose: We aimed to investigate RF-EMR-induced cell malignant transformation. Methods: We divided Balb/c-3T3 cells into sham and expo groups. The expo groups were exposed to a 1800 MHz RF continuous wave for 40 and 60 days, for 4 h per day. The sham group was sham-exposed. Cells were harvested for a cell transformation assay, transplantation in severe combined immune deficient (SCID) mice, soft agar clone formation detection, and a transwell assay. The mRNA microarray assay was used to declare key genes and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…It has been demonstrated that paracrine signaling from CAFs and myofibroblasts can regulate epithelial-mesenchymal plasticity, fibroblast activation, ECM modification and promote tumor progression and fibrosis [ 18 , 30 , 32 , 35 , 37 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been demonstrated that paracrine signaling from CAFs and myofibroblasts can regulate epithelial-mesenchymal plasticity, fibroblast activation, ECM modification and promote tumor progression and fibrosis [ 18 , 30 , 32 , 35 , 37 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the complexity of events that together contribute to chemical carcinogenesis, it is unlikely that a single method will be able to provide enough information about diverse events/mechanisms of actions and possible interactions [ 9 , 10 , 11 ]. Particularly, several studies have combined cellular transformation experiments using different cell lines with the transcriptome profiling, in order to explore the malignant transformation process [ 10 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation